Airway Pressure Release Ventilation in Adult Patients With Acute Hypoxemic Respiratory Failure: A Systematic Review and Meta-Analysis*. Issue 12 (December 2019) - Lim, Jolene; Litton, Edward
Abstract : Objectives: To evaluate the efficacy and safety of airway pressure release ventilation in critically ill adults with acute hypoxemic respiratory failure. Data Sources: A systematic literature search of MEDLINE via PUBMED, EMBASE, the Cochrane Library, published conference proceedings and abstracts, reference lists of eligible studies and review articles, and hand searches of relevant journals and trial registers. Study Selection: Eligible studies included randomized controlled trials published between years 2000 and 2018, comparing airway pressure release ventilation to any ventilation mode, in critically ill adults with acute hypoxemic respiratory failure and reporting at least one mortality outcome. Data Extraction: Screened citations were reviewed and extracted independently by two investigators onto a prespecified proforma. Data Synthesis: There were 412 patients from seven randomized controlled trials included in the qualitative and quantitative data synthesis. Airway pressure release ventilation was associated with a significant mortality benefit (relative risk, 0.67; 95% CI, 0.48–0.94; I 2 < 0.1%; p = 0.97) and improvement in day 3 PaO2 /FIO2 ratio (weighted mean difference, 60.4; 95% CI, 10.3–110.5). There was no significant difference in requirement to initiate rescue treatments including inhaled pulmonary vasodilators, prone positioning, or extracorporeal membrane oxygenation (relative risk, 0.51; 95% CI, 0.22–1.21; I 2 = 64.7%; p = 0.04). The risk of barotrauma was only reported in three studies and did not differ between groups (relative risk, 0.39; 95% CI, 0.12–1.19; I 2 < 0.1%; p = 0.99). Conclusions: In adult patients requiring mechanical ventilation for acute hypoxic respiratory failure, airway pressure release ventilation is associated with a mortality benefit and improved oxygenation when compared with conventional ventilation strategies. Given the limited number of patients enrolled in the available studies, larger multicenter studies are required to validate these findings. Abstract : Supplemental Digital Content is available in the text.